The genetic landscape of Parkinson's disease - Lunati, A.; Lesage, S.; Brice, A. (Revue neurologique, 2018)
The cause of Parkinson's disease (PD) remains unknown in most patients. Since 1997, with the first genetic mutation known to cause PD described in SNCA gene, many other genes with Mendelian inheritance have been identified. We summarize genetic, clinical and neuropathological findings related to the 27 genes reported in the literature since 1997, associated either with autosomal dominant (AD): LRRK2, SNCA, VPS35, GCH1, ATXN2, DNAJC13, TMEM230, GIGYF2, HTRA2, RIC3, EIF4G1, UCHL1, CHCHD2, and GBA; or autosomal recessive (AR) inheritance: PRKN, PINK1, DJ1, ATP13A2, PLA2G6, FBXO7, DNAJC6, SYNJ1, SPG11, VPS13C, PODXL, and PTRHD1; or an X-linked transmission: RAB39B. Clinical and neuropathological variability among genes is great. LRRK2 mutation carriers present a phenotype similar to those with idiopathic PD whereas, depending on the SNCA mutations, the phenotype ranges from early onset typical PD to dementia with Lewy bodies, including many other atypical forms. DNAJC6 nonsense mutations lead to a very severe phenotype whereas DNAJC6 missense mutations cause a more typical form. PRKN, PINK1 and DJ1 cases present with typical early onset PD with slow progression, whereas other AR genes present severe atypical Parkinsonism. RAB39B is responsible for a typical phenotype in women and a variable phenotype in men. GBA is a major PD risk factor often associated with dementia. A growing number of reported genes described as causal genes (DNAJC13, TMEM230, GIGYF2, HTRA2, RIC3, EIF4G1, UCHL1, and CHCHD2) are still awaiting replication or indeed have not been replicated, thus raising questions as to their pathogenicity. Phenotypic data collection and next generation sequencing of large numbers of cases and controls are needed to differentiate pathogenic dominant mutations with incomplete penetrance from rare, non-pathogenic variants. Although known genes cause a minority of PD cases, their identification will lead to a better understanding their pathological mechanisms, and may contribute to patient care, genetic counselling, prognosis determination and finding new therapeutic targets.